ANALISIS HUBUNGAN ANTARA FAKTOR SOSIODEMOGRAFI TERHADAP PENGGUNAAN CAM (COMPLEMENTARY ALTERNATIVE MEDICINE) PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BLABATUH II - Ni Nyoman Ayu Devi Suyeni; I Gusti Ayu Agung Septiari; Ni Putu Aryati Suryaningsih (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Hypertension is a global public health problem. As a chronic disease, hypertension requires long-term therapy. Patients with chronic diseases such as hypertension tend to seek other therapeutic options besides conventional therapy. One of the treatment options for chronic disease patients is Complementary Alternative Medicine (CAM). This study aims to determine the relationship between sociodemographic factors such as age, gender, education level, income level, and occupation with the use of CAM in hypertensive patients in Bali, especially at the Community Health Center Blabatuh II. This study used a cross-sectional design with the two-stage random sampling method. The research instrument was a questionnaire. A chi-square analysis was carried out to determine the association of each sociodemographic factor (age, gender, education level, income level, and occupation) with CAM use. Sixty (64.5%) respondents out of 93 respondents using CAM and 33 (35.5%) respondents did not use CAM for hypertension management. The sociodemographic factor that was significantly associated with CAM use was gender (); nevertheless, age, gender, educational level, and income level were not associated with CAM use in this study. Future research requires more diverse respondents as well as research on the relationship between factors other than sociodemographic such as sociocultural background, and perceptions of hypertension patients regarding the efficacy of CAM use with CAM use.